A Prospective Blinded Study Evaluating the Role of Endoscopic Ultrasound before Endoscopic Retrograde Cholangiopancreatography in the Setting of "Positive" Intraoperative Cholangiogram during Cholecystectomy. Issue 4 (April 2016) - Luthra, Anjuli K.; Aggarwal, Vipul; Mishra, Girish; Conway, Jason; Evans, John A.
During laparoscopic cholecystectomy, intraoperative cholangiography (IOC) is used to identify common bile duct (CBD) stones. In patients whose IOC is suspicious for stones, endoscopic retrograde cholangiopancreatography (ERCP) is the modality of choice for stone removal. However, IOC has a false positive rate of 30 to 60 per cent, and ERCP adverse events may occur in 11 per cent of patients. Endoscopic ultrasound (EUS) may serve as a noninvasive means of diagnosing suspected CBD stones. This study sought to assess the role of EUS in predicting the likelihood of choledocholithiasis at ERCP in patients found to have a positive IOC. This was a prospective blinded study of EUS before ERCP in patients with a positive IOC. Recruited subjects who underwent cholecystectomy and had an IOC with suspicion for obstruction were referred for ERCP within one month of their procedure. In patients with a positive IOC, EUS had a positive predictive value of 95 per cent in detecting choledocholithiasis. IOC with single or multiple filling defects more often correlated to the presence of CBD stones. At ERCP, choledocholithiasis was present in 65 per cent of patients who had an IOC suspicious for CBD stones. EUS should be used as a noninvasive method to correctly identify retained CBD stones in low-to-moderate risk patients with a positive IOC.